2020
DOI: 10.3390/agriculture10030083
|View full text |Cite
|
Sign up to set email alerts
|

Seed Dressing Maize with Imazapyr to Control Striga hermonthica in Farmers’ Fields in the Savannas of Nigeria

Abstract: Use of small doses of imazapyr and pyrithiobac for seed coatings of imazapyr-resistant maize hybrids (IR-Maize) offers an effective means to control Striga hermonthica. Field trials were conducted in Bauchi and Kano States of Nigeria in 2014 and 2015 under heavy Striga infestation to evaluate the potential effectiveness of herbicide coated hybrids maize on Striga control in farmers’ field. Results showed that herbicide coated seeds reduced number of emerged Striga per m2 and Striga damage symptoms in farmers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our results show that varieties or hybrids that are bred for low Striga emergence and damage produced higher grain yields in fields naturally infested with Striga, consistent with findings of Kamara [8]. In on-farm soybean maize rotation experiment in northern Nigeria, Kamara et al [21] reported that continuously grown Striga-resistant maize varieties produced grain yields similar to that of Striga-resistant maize variety grown after soybean but had higher grain yields than the local susceptible maize hybrids. The higher dry matter and grain yields recorded in the new DTSTR hybrids may be due to the combined effects of N application and lower Striga infection and damage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results show that varieties or hybrids that are bred for low Striga emergence and damage produced higher grain yields in fields naturally infested with Striga, consistent with findings of Kamara [8]. In on-farm soybean maize rotation experiment in northern Nigeria, Kamara et al [21] reported that continuously grown Striga-resistant maize varieties produced grain yields similar to that of Striga-resistant maize variety grown after soybean but had higher grain yields than the local susceptible maize hybrids. The higher dry matter and grain yields recorded in the new DTSTR hybrids may be due to the combined effects of N application and lower Striga infection and damage.…”
Section: Discussionsupporting
confidence: 88%
“…Several methods have been recommended for the control of Striga in maize. These include the use of Striga-tolerant or resistant maize cultivars [18][19][20], application of nitrogen particularly for poor soils [8,14,21,22), legume-maize rotation [23][24][25][26], herbicide seed coating [21,27]. Maize breeders at the International Institute of Tropical Agriculture (IITA) have considered breeding for polygenic resistance to S. hermonthica as a viable approach to provide durable protection to the crop against diverse parasite populations [19].…”
Section: Introductionmentioning
confidence: 99%
“…The subsistence farmers are usually the most severely affected. The extent to which S. hermonthica affects the growth of its host varies tremendously, depending on the level of host plant resistance/tolerance, extent of infestation, and the prevailing environmental conditions [9,10]. Resistance to Striga denotes the capability of the host plant to induce the germination of Striga seeds but prevents the parasite from attaching to the roots of the maize plants or kills the attached parasitic plants.…”
Section: Introductionmentioning
confidence: 99%
“…Combination between host resistance and Fusarium oxysporum-based mycoherbicide caused effective Striga reduction and increased crop yield [82]. Similarly, the reduction in Striga infestation achieved through seed coating of imazapyr-resistant hybrid maize can be significantly further increased by exploiting maize Striga-resistance [83]. Recently, combining conservation agriculture practices, such as cover cropping and fertilizer applications, with Striga-resistant varieties was found to alleviate Striga impact on rice and maize [84].…”
Section: Integrated Striga Management (Ism)mentioning
confidence: 99%